Thermal microclimate assessment in dairy cow milking parlors: Seasonal variations in temperature-humidity index and implications for heat stress - Dimo Dimov; Toncho Penev; Ivaylo Marinov (Veterinary World)
Background and Aim: Rising global temperatures and increasing humidity levels are intensifying the risk of heat stress (HS) in high-yielding dairy cattle. The temperature–humidity index (THI) is a standard metric for evaluating thermal stress in livestock. This study aimed to assess seasonal and diurnal variations in temperature, relative humidity, and THI within a milking parlor and determine their compliance with established thermal comfort thresholds for dairy cows.